Use of special skills in criminal proceedings - Pilyukov, Yurii (Actual problems of law (Aktual'ni problemi pravoznavstva), 2020)
Recently, new types and forms of specialized knowledge have been actively used in the investigation of crimes, the procedure for involving specialists in investigative actions has changed, and the grounds for the appointment of expertise. These circumstances require further investigation to determine the relevance of the article.